Avaliação da ansiedade e da autoestima em renais crônicos submetidos ao tratamento hemodialítico - Silva, Luciana Jerônimo De Almeida (2020)
Chronic renal failure is one of the main chronic diseases, considered a worldwide public health problem. Chronic kidney patients who undergo hemodialysis also live a long-term process, which can cause complications, limitations and changes in their daily lives, causing psychological alterations such as anxiety and changes in selfesteem. Thus, the objective of this study is to assess anxiety and self-esteem in chronic kidney patients undergoing hemodialysis in a renal replacement therapy service in a general hospital in a city in the south of Minas Gerais. This is a descriptive-analytical, cross-sectional, quantitative study, with 108 chronic renal patients undergoing hemodialysis. The study was approved by the Research Ethics Committee and data collection took place, through an interview, in the period from November to December 2018, with the following instruments: questionnaire with socioeconomic data, lifestyle and chronic illness, about the illness and treatment and major life events, Anxiety and Depression Scale (anxiety subscale) and Rosenberg's Self-Esteem Scale. For data analysis, descriptive statistics, Cronbach's alpha coefficient, Pearson's chi-square and Fisher's exact tests were used with a significance level of 5%. The odds ratio and logistic regression were estimated. As results, we found the same proportion of males and females, aged over 59 years, married or with partners, Catholics, with up to 2 children, with monthly family income from 1,001 to 2,500 reais. In addition, the time of diagnosis of chronic renal failure was up to two years, most had systemic arterial hypertension as a cause (cause), and up to two years of hemodialysis treatment. Most patients were classified without anxiety, highlighting a small percentage of people with anxiety.It was found that the variables time of hemodialysis treatment, remarkable events in life, monthly family income and type of access to perform hemodialysis showed a statistical association with the measure of anxiety. Most respondents had average self-esteem. However, a relevant percentage of these patients was classified as high self-esteem and a small percentage with low self-esteem. The variables monthly family income and length of treatment on hemodialysis showed a statistical association with the measure of selfesteem. The variables anxiety and self-esteem showed a statistical association, in which chronic kidney patients undergoing hemodialysis with anxiety were more likely to have medium / low self-esteem. It is expected that nursing professionals and the entire multidisciplinary team may be sensitized to provide comprehensive care to chronic kidney patients aiming for a better professional / client interaction, as well as improving the quality of the professional / client / family / institution relationship, to achieve better coping with the disease and treatment. This study can contribute to the development of strategies aimed at humanization and comprehensive care, with the objective of minimizing anxiety and increasing the self-esteem of chronic kidney disease patients during hemodialysis treatment.